PENGGUNAAN WAJAH MANDRA SEBAGAI STIKER WHATSAPP MENURUT UNDANG-UNDANG HAK CIPTA: The Use Of Mandra's Face As Whatsapp Stickers According To Copyright Law - Lady Vera Verev; Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2025)
WhatsApp is a communication platform that allows users to share messages, images, videos, GIFs, and stickers in the digital era. One of the most popular features among users is the use of stickers or GIFs that feature the faces of public figures. A common example in Indonesia is the use of a sticker with the portrait of actor Mandra, particularly a scene from the comedic television series Si Doel Anak Sekolahan, accompanied by the text "Sombong Amat" (So Arrogant). The problem formulated in this article is the use of Mandra’s portrait as a WhatsApp sticker constitutes copyright infringement under Indonesian Law No. 28 of 2014 on Copyright. The research uses a normative legal approach, relying on secondary data, with primary data as support. It is descriptive and draws conclusions using deductive reasoning. The results and conclusions are the use of Mandra’s portrait as a WhatsApp sticker constitutes a violation of Article 44, paragraph (1) of the Copyright Act. However, the definition of protected works can be interpreted in multiple ways, as WhatsApp stickers can be classified as both portrait works and cinematographic works.